Influence of Rolling and Ageing On Mechanical Properties of AA2195 Based Metal Matrix Composites - M, Srinivasa Rao.; Padal, K. T. Balaram (International Journal of Integrated Engineering, 2023)
The modern Aluminium based composites have a great demand in the field of aerospace applications due to their lightweight, high strength, high stiffness, and superior mechanical properties. The main objective is to fabricate the AA2195 composites through Medium Frequency Induction Furnace (MFIF) with Taguchi L16 design of experiments, hot rolling process and heat treatment of composites is done and then compare the mechanical properties of hot rolled and heat treated AA2195 composite with casted composite. It is analyzed the effects of reinforcements like graphite and boron carbide on the mechanical behaviors and microstructure of both AA2195 composites. The microstructures revealed that reinforcements were distributed uniformly throughout the composites. It observed that the elemental investigation on SEM and XRD for both the composites showed that formed intermetallic compounds (IMCs) helped refine the microstructure and further increased the mechanical properties. The hot rolled and heat-treated AA2195 composite fabricated at 8% B4C and 6% Gr exhibits the more enhanced ultimate tensile strength, hardness, and reduction in density, % elongation compared to the casted composite. The rolling process is used to reduce the porosity of the composite. In contrast, heat treatment enhances the composite’s mechanical properties like strength and hardness.